New antimicrobials - Mądry, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2004)
In the last years the incidence of nosocomial Gram-positive bacterial infections has continued to increase, including infections caused by MRSA (Methicillin Resistant Staphylococcus Aureus) and VRE (Vancomycin Resistant Enterococcus). Enterococcal infections are an especially difficult clinical problem. Enterococcus have either congenital or quickly increasing acquired resistance also against glycopeptides. Two new antimicrobials active against Gram-positive bacteria have been lately introduced: in 1999, quinupristin/dalfopristin and in 2000, linezolid. Linezolid demonstrates its activity most of all against staphylococci, enterococci and streptococci. Resistance to linezolid is rare. This drug is well tolerated and may be administered orally. In some severe enterococcal infections (especially E. faecium and faecalis) linezolid is the only effective antibiotic. Synercid (quinupristin/dalfopristin) activity is similar to that of linezolid, but it is inactive against Enterococcus faecalis. This article also presents a short review of other new antibiotics. Their clinical status is not defined yet. Daptomycin is active against Gram-positive pathogens, including those resistant to other antibiotics. Tigilcycline is the third generation of tetracyclines which is active against Gram-positive, Gram-negative and anaerobic bacteria. Faropenem is an orally given antibiotic the activity of which is comparable to that of carbapenems. Cefpirome is the fourth generation of cephalosporins active against both Gram-positive and Gram-negative pathogens. Levofloxacin is the third generation of chinolones the activity spectrum of which comprises Gram-positive and Gram-negative pathogens and moxifloxacin is the fourth generation of chinolones active against Gram-positive organisms.